Asturicystis havliceki sp. nov. (Echinodermata, Homostelea) from the Middle Cambrian of Bohemia (Barrandian area, Czech Republic) - Fatka,O.; Kordule,V. (Journal of the Czech Geological Society, 2001)
The new species Asturicystis havliceki sp. nov. from the Middle Cambrian Jince Formation of the Pribram-Jince Basin is proposed to commemorate the importance of Dr. Vladimir Havlicek's research for the recognition of the Barrandian Lower Palaeozoic.
Keywords: Echinodermata; Carpoidea; Cincta; Asturicystis; Middle Cambrian; Barrandian area; Czech republic